Oxide Coatings on Nickel-Rich Layered Cathode Active Materials for Thiophosphate-Based Solid-State Batteries - Kitsche, David; Justus Liebig University Giessen (My University, 2023)
Lithium-ion batteries (LIBs) lay the foundation of today’s portable electronics, which have profoundly changed modern society, providing mobile communication and many other functionalities. However, recently they have drawn even more attention, especially as energy storage devices for electric vehicles (EVs) which are expected to replace vehicles powered by an internal combustion engine in the long run. This has strongly driven the development of LIBs, which are approaching physical limits regarding their energy density. Solid-state batteries (SSBs) are regarded as a promising next-generation battery technology. They are hoped to enable higher energy densities by making use of a Li metal anode. Not containing a flammable liquid, they could also eventually turn out to be safer than LIBs. Among the classes of solid electrolytes (SEs) that could replace their liquid counterpart in conventional LIB cells, thiophosphates stand out due to their high ionic conductivities and favorable processability. The main drawback of thiophosphates is their low thermodynamic stability, leading to a number of incompatibility issues at both anode and cathode. On the cathode side of SSBs, severe thiophosphate oxidation has to be prevented by using protective layers, especially on the cathode active material (CAM). Many such CAM coatings have been proposed in the past and were shown to have functionalities beyond preventing SE oxidation. Moreover, different methods have been used to deposit these layers on CAMs, each with different capabilities regarding the achievable coating thickness and morphology. The aim of this doctoral project was to prepare, characterize, optimize and test protective CAM coatings on LiNi0.85Co0.10Mn0.05O2, a Ni-rich NCM-type CAM, for use in thiophosphate-based SSB cells. The work resulted in publications on three different metal oxide coatings. Two of them are based on the use of atomic layer deposition (ALD), a method that previously had rarely been employed for this application. Nanometer-thin, conformal and adjustable layers of the binary oxides HfO2 and ZrO2 could be obtained. The coatings are nanocrystalline and beneficial for the cycling performance of the NCM CAM, especially when a post-heat treatment at moderate temperatures is performed. A systematic characterization of the ZrO2@NCM after heat treatment at temperatures ranging between 300 and 700 °C revealed a multifaceted evolution of the (sub)surface layer. This includes changes in crystallinity and a reaction between substrate and coating. The two studies showed that ALD is a viable tool to prepare high-quality model-type coatings that are well-suited for systematic investigations into the property-performance relationships and thereby advance the understanding of the working principles of CAM coatings. Apart from that, a facile wet chemical method was used to deposit a composite oxide coating consisting of Li3NbO4 nanoparticles and Li2CO3. This protective layer enabled excellent cycling performance regarding reversible specific capacity and rate capability (212 and 150 mAh/gCAM at 0.2 and 2.0 mA/gCAM, respectively) as well as stability (more than 80% capacity retention after 200 cycles). In doing so, the coating compared favorably to common lithium niobate coatings, thus showing that there is still room for improvements when it comes to wet chemical coating methods and CAM coatings in general.
Keywords: Solid-State Batteries; Cathode Active Material; Thiophosphates; Atomic Layer Deposition; Sol-Gel Method; Lithium-Ion Batteries; Interfaces; ddc:333.7; ddc:530; ddc:540; ddc:600